LEGAL ASPECTS OF THE ARMENIAN-TURKISH NEGOTIATION PROCESS - Danielyan, Gevorg (State and Law, 2022)
Legal aspects of the Armenian-Turkish negotiation process. -Entitled "Legal Aspects of the Armenian-Turkish Negotiation Process", this scholarly article is devoted to the study of the legal aspects of the key issues that are currently causing serious controversy, leading to conflicting approaches.The article touches upon the peculiarities of the current process from the previous three attempts to normalize the Armenian-Turkish relations since independence, the most significant conclusions reflected in the analysis of international and domestic experts, the legal bases, the main directions of their improvement, the legal tools to avoid possible negative consequences. the role of the Diaspora in terms of conditions, etc.According to the results of the research, a number of conclusions were put forward in line with the current process.
Keywords: Armenian-Turkish negotiation process; Meghri corridor; Armenian Genocide; Shushi declaration; contract law; preconditions